(untitled) (International journal of artificial intelligence, 2024)
Laparoscopic rectopexy is a type of surgery that is commonly performed to repair a rectal prolapse. This condition is characterized by a protrusion of the rectum through the anus, often caused by a weakness or total loss of the normal support structures of the rectum. Rectal prolapse presents with a variety of symptoms, including bleeding, acute pain, mucus drainage, and fecal incontinence. While it can result in serious discomfort and disruption to a person’s life, a rectal prolapse is completely treatable with laparoscopic rectopexy, a minimally invasive surgery that is designed to repair the damaged or weakened rectal support structures. Being a laparoscopic procedure, rectopexy surgery is typically performed through a very small incision made in the abdomen. Once the laparoscope is positioned, the surgeon will begin the process of repositioning the rectum. During this portion of the rectopexy procedure, the surgeon will carefully free the rectum from its surrounding support structures and lift it into the proper position. In most cases, stiches and mesh will be used to secure the rectum in place. To complete the procedure, the incision will then be closed using stiches.